The effect of simulated obstructive apnea and hypopnea on aortic diameter and BP. - Stöwhas, A; Namdar, M; Biaggi, P; Russi, E; Bloch, K; Stradling, JR; Kohler, M (2011)
BACKGROUND: Preliminary evidence supports an association between obstructive sleep apnea (OSA) and thoracic aortic dilatation. The mechanisms through which OSA may promote thoracic aortic dilatation are incompletely understood. Therefore, we studied the acute effects of simulated apnea and hypopnea on aortic diameter and BP in humans. METHODS: The diameter of the aortic root was measured in 20 healthy volunteers by echocardiography, and peripheral BP was continuously recorded prior, during, and immediately after simulated obstructive hypopnea (inspiration through threshold load), simulated obstructive apnea (Müller maneuver), end-expiratory central apnea, and normal breathing in randomized order. RESULTS: Proximal aortic diameter increased significantly during inspiration through a threshold load (+6.48%; SE, 3.03; P = .007), but not during Müller maneuver (+3.86%; SE, 2.71; P = .336) or end-expiratory central apnea (+0.62%; SE, 2.94; P = .445). Maneuver-induced changes in mean BP were observed during inspiration through a threshold load (-10.5 mm Hg; SE, 2.2; P < .001), the Müller maneuver (-8.8 mm Hg; SE, 2.4; P < .001), and end-expiratory central apnea (-4.2 mm Hg; SE, 1.4; P = .052). There was a significant increase in mean BP on release of threshold load inspiration (+8.1 mm Hg; SE, 2.9 mm Hg; P = .002), Müller maneuver (+10.7 mm Hg; SE, 2.9; P < .001), and end-expiratory central apnea (+10.6 mm Hg; SE, 2.5; P < .001). CONCLUSIONS: Simulated obstructive hypopnea/apnea and central apnea induced considerable changes in BP, and obstructive hypopnea was associated with an increase in proximal aortic diameter. Further studies are needed to investigate effects of apnea and hypopnea on transmural aortic pressure and aortic diameter to define the role of OSA in the pathogenesis of aortic dilatation.